Improvement of an interobserver agreement of ARDS diagnosis by adding additional imaging and a confidence scale - Hagens, Laura A.; Van der Ven, Fleur L. I. M.; Heijnen, Nanon F. L.; Smit, Marry R.; Gietema, Hester A.; Gerretsen, Suzanne C.; Schultz, Marcus J.; Bergmans, Dennis C. J. J.; Schnabel, Ronny M.; Bos, Lieuwe D. J. (Frontiers in Medicine, 2022)
Acute respiratory distress syndrome (ARDS) often is not recognised in clinical practice, largely due to variation in the interpretation of chest X-ray (CXR) leading to poor interobserver reliability. We hypothesized that the agreement in interpretation of chest imaging for the diagnosis of ARDS in invasively ventilated intensive care unit patients between experts improves when using an 8-grade confidence scale compared to using a dichotomous assessment, and that the agreement increases after adding chest computed tomography (CT) or lung ultrasound (LUS) to CXR. Three experts scored ARDS according to the Berlin definition based on case records from an observational cohort study using a dichotomous assessment and an 8-grade confidence scale. The intra class correlation (ICC) was calculated per day, imaging modality, and scoring method and compared using bootstrapping. A consensus judgement on the presence of ARDS was based on the combined confidence grades of the experts, followed by a consensus meeting for conflicting scores. 401 patients were included in the analysis. The best ICC was found using an 8-grade confidence scale for LUS (ICC: 0.49; 95%-CI: 0.29 to 0.63) and CT evaluation (ICC: 0.49; 95%-CI: 0.34 to 0.61). The ICC of CXR increased by 0.022 and of CT by 0.065 when 8-grade scoring was used instead of dichotomous assessment. Adding information from LUS or chest CT increased ICC with 0.25, when using the 8-grade confidence assessment. Agreement on diagnosis of ARDS can increase substantially by adapting the scoring system from dichotomous to an 8-grade confidence scale and by adding additional imaging modalities such as LUS or chest CT. This suggests that a simple assessment of ARDS presence by a chart review of one assessor is insufficient to define ARDS in future studies.